Estudo da fábula: contexto linguagem e representação - Farencena, Gessélda Somavilla (2011)
This paper assumes that language is the primary means of socialization of individuals. Considering its functionality, more than just allowing the simple exchange of information, it allows us to establish interpesonal relationships, to express and to build representations of experiences. Thus, this study presents an analysis of seven fables originally attributed to Aesop and seven versions revisited by Millôr Fernandes. With twenty-five-century distant productions, these texts are studied from the perspective of its Generic Structure Potential (GPS), in order to examine, through contextual and lexical-grammatical description, the representations of the characters in Aesop‟s and Millôr Fernandes‟s fables. For this, the fundamental theoretical assumptions used are notion of genre from Hasan (1989), the concept of situational context from Halliday (1989), the lexical-grammatical categories of the transitivity system from the Systemic Functional Grammar from Halliday & Matthiessen‟s (2004 ), the lexico-semantical categories of the Appraisal Theory from Martin & White (2005), the theory of social representations from Moscovici (2009) and the three-dimensional model from Fairclough (2001). The results show that, concerning to the genre, fables produced by Millôr Fernandes presented a stage we call [E # 3.3] Consummation and / or continuation to completion, nonexistent in Aesopian‟s fables, which brings different outcomes. In relation to the social contexts in which the fables were produced, the analysis showed similarities and differences when regarding to situations of oppression experienced by Aesop in the conditions of a slaver, and the ones lived by Millor Fernandes during the Brazilian Military Dictatorship. Moreover, the nature and consequences of these oppressions are distinct in the context of each author. In relation to the linguistic analysis, the lexico-grammatical roles played by the main characters, and the evaluations expressed by the marks of affection, trial, assessment and force point to representations such as reflections of cultural and situational contexts experienced by fabulists. In Aesop's fables, the characters represented as the winners, who have achieved their goals, use more the imposing of physical strength than their linguistic resources. In the fables of Millor Fernandes, instead, the victorious characters use more of the resources of language to overcome the strongest ones. In this sense, the representation pointed to the classical society is that the force stood out the word, being used more frequently and efficiently. The representation that is configured to the contemporary society of Millôr, however, is that language is used as the main resource for solving problems and overcoming the strongest ones.